KEBIJAKAN KEAMANAN PANGAN PRODUK PERIKANAN: FAKTOR-FAKTOR PENYEBAB PENGGUNAAN FORMALIN OLEH PENGOLAH IKAN TRADISIONAL : STUDI KASUS PANTAI UTARA JAWA BARAT, DKI JAKARTA, DAN BANTEN - Aef Permadi; Mita Wahyuni; Daniel R. Monintja; Sunarya Sunarya; Agus Heri Purnomo (Buletin PSP, 2007)
Fish products (processed and iced) in the domestic market have been contaminated by formalin that caused by misuse of formalin in processing or handling practice of fish product. This fact clearly is threatening to public health. Therefore development of policy on preventive use of formalin is needed. The objective of the research is to find determining factors of formalin misuse by traditional fish processors. The result of this research is expected to lead to formulation of an effective appropiate policy, not only for preventing the use of formalin but also many other unhealthy processing practices. The research was conducted within the periode of March 2005 to Mei 2006 at Cirebon, Indramayu, Subang, Karawang, Jakarta, and Tangerang. Proportionate random sampling was used to allocate sampling points. Data analysis was conducted using Factor Analysis. The results show that there are 13 factors which fall into 2 principle components. There are 9 variables in the 1st principle component i.e., law enforcement, economic, formalin price, friend’s influence, monitoring, guidance, consumer, distribution of formalin, and religion. Meanwhile, there are 4 variables in the 2nd principle component i.e., storage life, quality, yield, and alternative technology